"y''+2y'+y=3e^{-t}\\\\\ny(0)=4, y'(0)=2\\\\"
Solution of equation find in form
"y=y_1+y_2"
Consider equation
"y''+2y'+y=0"
Write characteristic equation
"\\lambda^2+2\\lambda+1=0 \\to \\lambda_1=\\lambda_2=-1"
then the solution of equation is
"y_1=c_1e^{-t}+c_2te^{-t}"
The solution "y_2" find in form
"y_2=at^2e^{-t}"
input "y_2" in the first equation
"2ae^{-t}-2tae^{-t} -2tae^{-t} +t^2ae^{-t}+\\\\\n+4tae^{-t}-2t^2ae^{-t}+t^2ae^{-t}=3e^{-t}\\\\\n2a=3 , a=1.5"
so
"y_2=1.5t^2e^{-t}"
and
"y=c_1e^{-t}+c_2te^{-t}+1.5t^2e^{-t}"
Find
"y'=-c_1e^{-t}+c_2e^{-t}-c_2te^{-t}+\\\\\n+2t\\cdot 1.5e^{-t}-1.5t^2e^{-t}\\\\\ny(0)=c_1 \\to c_1=4\\\\\ny'(0)=-c_1+c_2 \\to -c_1+c_2=2 \\to\\\\\n-4+c_2=2 \\to c_2=6"
So
"y=4e^{-t}+6te^{-t}+1.5t^2e^{-t}"
Comments
Leave a comment